Responsabilidade tributária dos sócios e administradores: natureza, limites e execução fiscal - Teixeira, André Nobre (2014)
The responsibility of the business societies’ partners is case of responsibility of third, it regulated by the articles 134 and 135 of the National Tributary Code, complementary norm ratione materiae, according to the Republic Book Constitution determines, in the article 146, provision III, line b. The quoted legal devices have been being applied from contradictory form by our courts, it occurring, many times, the redirection of the tributary obligation to the partners, without, nevertheless, the legal requirements are configured. It searches to do a doctrinaire analysis of the legal norm, facing it with the STJ’s jurisprudence. It is possible to say that the STJ’s jurisprudence has been walking, slowly, in direction of the doctrinaire position.